1980
DOI: 10.1002/kin.550121005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the mechanism of the oxidation of the trichloromethyl radical by the photolysis of chloral in the presence of oxygen

Abstract: The photooxidation of chloral was studied by infrared spectroscopy under steady-state conditions with irradiation of a blackblue fluorescent lamp (300 nm < X < 400 nm, A,, = 360 nm) at 296 f 2 K. The products were hydrogen chloride, carbon monoxide, carbon dioxide, and phosgen. The kinetic results reveal that the reaction proceeds via chain reaction of the C1 atom:(1)The results lead to the conclusion that mechanism (B) is confirmed to be more likely than mechanism (A), which was favored at one time by Heickle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…Figure 2a illustrates the quasi linear increase of CCl 2 O, in agreement with eq I. [32][33][34][35] The results for k 1 are summarized in Table 5. In contrast to systems studied previously in our laboratory, 9,18,[37][38][39][40][41] the kinetic data were not derived by following the decay of the peroxy radical, but were instead derived by monitoring the appearance of the product, CCl 2 O.…”
Section: A the CCL 3 O 2 And Chcl 2 O 2 Uv Absorption Spectrasupporting
confidence: 75%
See 1 more Smart Citation
“…Figure 2a illustrates the quasi linear increase of CCl 2 O, in agreement with eq I. [32][33][34][35] The results for k 1 are summarized in Table 5. In contrast to systems studied previously in our laboratory, 9,18,[37][38][39][40][41] the kinetic data were not derived by following the decay of the peroxy radical, but were instead derived by monitoring the appearance of the product, CCl 2 O.…”
Section: A the CCL 3 O 2 And Chcl 2 O 2 Uv Absorption Spectrasupporting
confidence: 75%
“…Several end-product studies at room temperature [32][33][34][35] have shown that the self-reaction leads to the Cl 2 (or F 2 ) + hν (λ > 300 nm) f 2Cl (or 2F) Kinetics of the CCl 3 O 2 Self-Reaction.…”
Section: A the CCL 3 O 2 And Chcl 2 O 2 Uv Absorption Spectramentioning
confidence: 99%
“…Atmospheric COC12 is produced from the oxidation of chlorinated ethenes and ethanes [Ohta and Mizoguchi, 1980;Nelson et al, 1984;, and a review of the known source strengths of these compounds suggests that the major contributors to this production are C2C14, C2HC13, CHC13, CH3CC13, and CC14 [Singh, 1976;Wilson et al, 1988;Tuazon et al, 1988;Helas and Wilson, 1992]. As was noted earlier, these compounds fall into two genetic classes: the RPP compounds, which react with OH and absorb in the UV and thus can produce COCI: in both the troposphere and the stratosphere, and CC14, which does not react with OH in the troposphere and thus produces COCI: only in the stratosphere.…”
Section: The Production Of Phosgenementioning
confidence: 99%
“…The oxidation of C13C• from the photolysis of chloral has been proposed to follow a pathway analogous to steps 7 and 8. 31 Reaction via steps 10-13 is expected to be very minor, since Cl3SiOOH was not detected even under low-tempera ture photolyses. Additionally, such a pathway would require the conversion of one-third of the silane hydrogens to HCl.…”
Section: Discussionmentioning
confidence: 99%
“…An oxidizing intermediate, presumed to be Cl3COOH, was detected while the intermediate alcohol, Cl3COH, was assumed to decompose to HCl and C12C0.8,32 Similarly, the radical, Cl3CO•, is proposed to decompose to Cl2CO and Cl. 31 The silanol, Cl3SiOH, and siloxyl radical, Cl3SiO•, appear to be thermodynamically more stable than their carbon analogues because of silicon's disinclination to form multiple bonds. 33 Ozone is known to react readily with silanes to form silanols and siloxanes.34 A mechanism to be considered as an alternative to that proposed above is one including ozone as an intermediate formed by the photolysis below 240 nm and subsequent reactions of molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%